Synthesis, Spectroscopic, Biological Screening of Mn (II) and Cu (II) Complexes with Cysteine - Srivastava, Vinay Kumar; Rani, Khushboo (International Journal of Pharmaceutical Investigation, 2025)
Objectives Cysteine is a promising ligand for synthesizing complexes with Mn (II) and Cu (II) ions. The main objectives of the study were to synthesize, characterize and examine the Biochemical behavior of metal complexes. Materials and Methods Metal complexes were synthesized by adding a methanolic solution of ligand (1 mmol) to manganese Chloride/Copper acetate (1 mmol). The resulting mixture was stirred magnetically for 4-5hr at room temperature. The complexes were then filtered, washed with ethanol followed by ether and dried. Results The resulting complexes were investigated by the help of elemental analysis, Molar Conductance, IR, Electronic, NMR Spectral Studies and biological Studies. Conclusion The transition metal complexes have been obtained by the treatment of Sodium salt of L-cysteine ligand with metal acetate/chloride. Complexes under investigation have shown antibacterial, antifungal and potential anticancer activities.
Keywords: Anticancer activity; Biocidal; Spectra; Synthesis